Tantangan dan Peluang Dalam Pengajaran Bahasa Inggris: Studi Kasus di Politeknik Masamy Internasional Banyuwangi - Mainike Silvi Rety Badian; Setyorini Dwi Agustini; Ike Meilani Fajarsari (LP. Ma'arif Janggan Magetan, 2024)
English language teaching at the vocational education level, such as at Politeknik Masamy Internasional Banyuwangi, faces unique challenges and opportunities in the context of developing language competence for students. This study aims to analyze the challenges faced by lecturers and students and explore the opportunities that can be leveraged to improve the effectiveness of English language teaching at Masamy International Polytechnic of Banyuwangi. The study used a qualitative approach with a case study method involving interviews with lecturers and students as well as classroom observations. The findings show that the main challenges in teaching English at Masamy International Polytechnic of Banyuwangi include limited learning facilities, differences in students' language proficiency levels, and students' lack of motivation to learn English in depth. However, opportunities to overcome these challenges are also wide open through the use of educational technology, curriculum development that is more contextual and relevant to industry needs, and increased training for teachers. The results of this study are expected to provide useful references for the development of teaching strategies at Politeknik Masamy Internasional Banyuwangi and other vocational education institutions.